Insight on Theoretical and Conceptual Review on the Diffusion of Innovative Marketing Digital Transformation Systems in Circular Economy Era - Julius Jillbert; Andi Nur Baumassepe; Amaluddin Fatih Ghurron; Valentino Aris (www.amertainstitute.com, 2023)
This article is related to the diffusion of innovations, especially those known based on the Innovation Diffusion Theory or IDT which states that in general diffusion behaviour can be defined through individual perceptions regarding the use of certain innovations. The basic definition of diffusion gives rise to different understandings in two research streams. First, in economics and non-marketing disciplines, diffusion is seen as the spread of an innovation over time among different groups (Brown, 1981). While the second in the marketing discipline, diffusion refers to